The significance of holistic marketing on motivations, expectations and experiences of travellers: A case study on Queenstown’s first-time tourists - Master, Arnaz (Auckland University of Technology, 2018)
This thesis investigates the significance of holistic marketing on tourist motivations, expectations, and experiences through a case study of Queenstown, New Zealand. Queenstown’s marketing initiatives and tourism operations were researched and critiqued to reveal a lack of holistic marketing. To investigate the impact of this lack of holistic marketing, a survey of 250 first-time tourists was conducted to collect raw data on tourists’ pre-arrival knowledge, motivations, and expectations, as well as tourists’ post-arrival experiences and recommendations. Raw data from this survey was analysed to reveal discrepancies in Queenstown’s marketing. It was found that due to the limitation and selective destination marketing of Queenstown’s Top 3 tourism offerings, first-time visitors were kept from understanding the destination’s holistic nature. Results acquired from these surveys showed the impact of marketing practices on tourists’ pre-arrival expectations. These expectations were shown to impact tourists’ satisfaction levels. Tourists experienced overall positive disconfirmation, however, tourists’ reported highlights of experiences suggested otherwise when compared to their primary aims for visiting. Results revealed that holistic marketing of Queenstown’s offerings would further enhance tourist experiences, and development of under-rated offerings and operations would benefit the destination through improving quality and allowing for increased marketing. This research concluded with the recognition that holistic marketing is a tactical activity that destination marketers need to strategically implement in order for it to have a long-term and sustainable tourism activity.
Keywords: Tourism; Tourism marketing; Holistic marketing; Significance of marketing; Motivations; Expectations; Experiences; First-time tourists; Queenstown; New Zealand; Expectancy Disconfirmation Theory; EDT